EPIGENETIC AND GENETIC ASPECTS OF THE PHENOTYPES OF PRADER-WILLI AND ANGELMAN SYNDROMES - Fedoniuk, L.Ya.; Kovanova, E.N.; Remynetskii, B.Ya.; Yeroshenko, G.A.; Vatsenko, A.V.; Perederii, N.O.; Улановська-Циба, Н.А.; Khannanova, O.R. (World of Medicine and Biology, 2020)
The study of the epigenetic and genetic mechanisms of genomic imprinting and single-parent dysomia, as the most common disorders in Prader-Willi syndrome and Angelman syndrome, contributes to the discovery of the pathogenesis of these genetic anomalies and provides a basis for searching for new methods for their prevention and epigenetic therapy. Monoallelic expression of genes in genomic imprinting develops due to different methylation of 15 chromosome DNA, which is specific for different sexes. Prader-Willi syndrome develops as a result of microdeletion at the q11-q13 locus and the mutation of the candidate gene SNRPN of the paternal chromosomes. Angelman syndrome – as a result of microdeletion at the locus q11-q13 and mutation of the candidate gene UBE 3A in the maternal chromosome. The father's single-parent dysomia becomes the cause of Angelman syndrome, and the mother's single-parent dysomia is the cause of Prader-Willi syndrome. It can be assumed that similar Prader-Willi syndrome and Angelman syndrome disorders of genomic imprinting can arise as a result of demethylation of female and male chromosomes with the help of methyltransferases.